A stick-slip piezoelectric actuator with an integrated sensing unit for the measurement and active control of the contact force. (May 2023) - Chen, Weiwei; Wei, Dayu; Mei, Yubing; Xu, Zhi; Sun, Qiang; Liu, Yanwei; Huang, Hu
Abstract: Output characteristics of the stick-slip piezoelectric actuators are intrinsically affected by the contact force between the driving foot and the mover. Therefore, it would be quite meaningful to measure and control the contact force. In this study, by integrating a group of strain gauges into the driving compliant mechanism, a stick-slip piezoelectric actuator with measured contact force was proposed. The main structural parameters of the driving compliant mechanism were designed and analyzed. Through experiments, the sensing unit was calibrated, and the results showed that it had good linearity, and the noise level was 3.5 mN. The contact force was measured by the sensing unit, and accordingly, the relationship between the contact force and the stepping characteristic was explored. It was shown that the change in contact force would lead to the evolution in stepping characteristic, which finally resulted in the motion nonlinearity of the actuator in large stroke output. Accordingly, by actively controlling the contact force, a method was proposed to tune the stepping characteristic. The comparative results demonstrated that this method could significantly improve the motion linearity of the actuator in large stroke output under various preloads and even very rough surface.